2016
DOI: 10.1111/adb.12483
|View full text |Cite
|
Sign up to set email alerts
|

d‐Cycloserine enhanced extinction of cocaine‐induced conditioned place preference is attenuated in serotonin transporter knockout rats

Abstract: d-Cycloserine (DCS), a partial NMDA receptor agonist, has been proposed as a cognitive enhancer to facilitate the extinction of drug-related memories. However, it is unknown whether there are individual differences in the efficacy of DCS. Here, we set out to investigate the influence of serotonin transporter (5-HTT) genotype on DCS treatment outcome and the underlying neural mechanism. To that end, we first determined the mRNA levels of several NMDA receptor subunits and observed a reduction in NR1/NR2C recept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 50 publications
1
14
0
Order By: Relevance
“…In line with our previous results (Karel et al 2018), we observed a significant effect of genotype (F1,52=9.739, p<0.01) and of age (F1,52=19.420, p<0.001) on GluN1 gene expression ( Fig.1A). Indeed, even if the changes observed across ages were similar for the two genotypes, the mRNA levels of the mandatory subunit of the NMDA receptor were significantly reduced in SERT -/compared to SERT +/+ rats from PND21 (-38%, p<0.05 vs SERT +/+ ) and PND100 (-14%, p<0.05 vs SERT +/+ ).…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…In line with our previous results (Karel et al 2018), we observed a significant effect of genotype (F1,52=9.739, p<0.01) and of age (F1,52=19.420, p<0.001) on GluN1 gene expression ( Fig.1A). Indeed, even if the changes observed across ages were similar for the two genotypes, the mRNA levels of the mandatory subunit of the NMDA receptor were significantly reduced in SERT -/compared to SERT +/+ rats from PND21 (-38%, p<0.05 vs SERT +/+ ) and PND100 (-14%, p<0.05 vs SERT +/+ ).…”
Section: Resultssupporting
confidence: 93%
“…This was associated with reduced expression of various GABAergic markers that we independently also found to be reduced in the prefrontal cortex from early life to adulthood (Guidotti et al 2012;Calabrese et al 2013). Moreover, according to the observation that brain function depends on an intricate balance between excitation and inhibition (Zafra et al 1991), we recently reported that SERT -/rats display increased expression of the glutamatergic GluN2A subunit and reduced expression of the GluN1 receptor subunit in the prefrontal cortex (Karel et al 2018).…”
Section: Introductionmentioning
confidence: 75%
“…Interestingly, LgA cocaine self-administration strongly reduced SLC1A2 expression in SERT +/+ , an effect that was not observed in SERT -/rats, suggesting that removal of SERT in cocaine-naïve animals leads to molecular features that are observed also following LgA cocaine self-administration. Taking into account that SLC1A2 reduction may promote cocaine seeking (see: Knackstedt et al, 2010), these findings reveal that the life-time deletion of SERT, by long-lastingly reducing Hb SLC1A2 expression, may contribute to make SERT -/rats more prone to self-administer cocaine (Homberg et al, 2008;Karel et al, 2018;Nonkes et al, 2011;Verheij et al, 2018).…”
Section: Discussionmentioning
confidence: 92%
“…These observations are critical since accumulating evidence implicate Hb in the pathogenesis of serotonin-related disorders such as anxiety, depression and possibly drug addiction. SERT -/rats self-administer much more cocaine than their wild-type littermates suggesting that changes in central extracellular 5-HT levels facilitate cocaine selfadministration (Homberg et al, 2008;Karel et al, 2018;Nonkes et al, 2011;Verheij et al, 2018) . This increased cocaine self-administration is associated with increased anxiety-related behavior during withdrawal (Verheij et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation